KEEFEKTIFAN PROPOLIS PADA PENDERITA KANDIDIASIS ORAL - Lingling Marinda Palupi (Jurnal Informasi Kesehatan Indonesia (JIKI), 2018)
The limitations of antifungal drugs due to resistance, especially in HIV patients are things that need attention. The development of antifungal drugs as an alternative of oral candidisasis needs to be done, one that can be used as an alternative for treatment is propolis. This literature review explains the effectiveness of non-pharmacological antifungal therapy with propolis treatment in patients with oral candidiasis. The articles discussed in the literature review were taken from the Google Scholar, SpringerLink, ScienceDirect, Sage Journals Online and ProQuest databases, within the limits of 2002-2017. The next step is article evaluation, then the compilation of literature reviews from 4 selected article titles in accordance with the author's inclusion criteria. The inclusion criteria in this review were based on PICO (P: oral candidiasis lesions; I: propolis; C: antifungal drugs; O: propolis effectiveness). The four articles have similar results. The similarity of the results is the positive effect of giving propolis with various types of Candida. Propolis which in the discussion of the article uses propolis ethanol extract (EPE) with various processing methods to produce good performance effects. This therapy is actually considered cheaper and more natural than antifungal agents that have been standardized with no less good effectiveness. Keywords: oral candidiasis, antifungi, propolis